1997
DOI: 10.1097/00006842-199701000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Slowing and Working Memory Difficulties in Chronic Fatigue Syndrome

Abstract: It is concluded that, although CFS and major depression and dysthymia have distinct clinical features, these disorders have slowed motor and cognitive processing speed in common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
71
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 33 publications
15
71
2
Order By: Relevance
“…This finding is in accordance with previous reports indicating alterations in working memory, including the SWM task of the CANTAB, in patients with CFS (Joyce et al, 1996;Marshall et al, 1997). In addition, CFS patients with One CFS subject with significant mental fatigue missed all target sequences, and therefore did not obtain any values for these measurements.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in accordance with previous reports indicating alterations in working memory, including the SWM task of the CANTAB, in patients with CFS (Joyce et al, 1996;Marshall et al, 1997). In addition, CFS patients with One CFS subject with significant mental fatigue missed all target sequences, and therefore did not obtain any values for these measurements.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is supported by previous data indicating reduced information-processing speed in CFS patients (Marshall et al, 1997(Marshall et al, , 1999. CFS patients with significant mental fatigue did not show, however, any significant slowing in tasks requiring lower cognitive demand/control, including the task of simple and choice RTI and PRM.…”
Section: Discussionsupporting
confidence: 89%
“…This finding therefore supports those of other authors who have also provided objective evidence for poor attention within the CFS population (McDonald et al 1993 ;Ray et al 1993 ;Sandman et al 1993 ;Cope et al 1995 ;Marshall et al 1997 ;Johnson et al 1998). The impairment the CFS group showed in attention was not accounted for by differences in mood.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to increased physical symptoms after exercise, cognitive function did not deteriorate over time although many studies have reported impairment in cognitive function at baseline (22)(23)(24) or after exercise (11,12,25) for patients with CFS. The reason for this discrepancy may relate to our use of the continuous performance test in this study although one of our previous studies showed that exercise did not alter cognitive function (26).…”
Section: Discussionmentioning
confidence: 82%